2005
DOI: 10.1016/j.jtcvs.2004.12.041
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the erythropoietin receptor in human heart

Abstract: rythropoietin (EPO), the kidney hormone regulating erythrocyte production, activates the erythropoietin receptor (EPOR), resulting in antiapoptosis. To investigate the clinical significance of EPOR expressed in neuronal cells of the brain, EPO was administered to patients within 8 hours of the onset of stroke symptoms, which ultimately resulted in the reduction of cerebral infarct size and improvement of functional neurologic performance. 1 Rodents treated with EPO in an animal model of myocardial ischemia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 5 publications
0
39
0
1
Order By: Relevance
“…22 EPO is expressed by hypoxic -ischemic endothelial cells and myocytes, 10 whose EPO receptors 30,31 make them potential targets of EPOmediated endocrine and paracrine/autocrine activity. It was reported that EPO receptor is present on the surface of human endothelial cells 32 and ventricular myocytes, 31 and that administration of EPO inhibits hypoxia-mediated apoptosis of endothelial cells 33 and cardiomyocytes 34 by activating PI3/ Akt pathway. Experimental studies have shown that EPO induces an anti-apoptotic metabolic shift that protects against hypoxic injuries and enhances cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…22 EPO is expressed by hypoxic -ischemic endothelial cells and myocytes, 10 whose EPO receptors 30,31 make them potential targets of EPOmediated endocrine and paracrine/autocrine activity. It was reported that EPO receptor is present on the surface of human endothelial cells 32 and ventricular myocytes, 31 and that administration of EPO inhibits hypoxia-mediated apoptosis of endothelial cells 33 and cardiomyocytes 34 by activating PI3/ Akt pathway. Experimental studies have shown that EPO induces an anti-apoptotic metabolic shift that protects against hypoxic injuries and enhances cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…Epo receptors and functional responses to Epo were shown in isolated cardiomyocytes (141,(143)(144)(145)(146) coronary endothelial cells (83, 147) and fibroblasts (148). The cardiac EpoR was shown to respond equally efficiently to Epo, carbomylated Epo (CEPO), and ARA-290 (141,149,150), a synthetic Epo mimetic comprised only of helix B part of the cytokine.…”
Section: Epo In Treatment Of Brain Diseasesmentioning
confidence: 99%
“…The presence of EPO receptors on vascular cells (endothelial and smooth muscle cells) indicates that EPO has a direct vascular effect on vessels (Depping et al 2005). EPO increases vascular tone by increasing intracellular calcium content (Schiffl and Lang 1997).…”
Section: Discussionmentioning
confidence: 99%